Public Relations Management Strategies in Improving School Image - Abdul Ghofur; Moh Rofiki (FASHLUNA, 2026)
School image is an important factor in increasing public trust in educational institutions. However, some schools still experience obstacles in building a positive image due to suboptimal public relations management, such as limited public communication, low community involvement, and less than optimal use of information media. This study aims to analyze public relations management strategies in improving school image at Nurul Falah Vocational School in Bondowoso Regency. This study uses a qualitative approach with a descriptive research type. Data collection techniques were carried out through interviews, observation, and documentation involving the principal, public relations team, teachers, education staff, parents, and the surrounding community as research informants. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that public relations management strategies at Nurul Falah Vocational School are carried out through systematic public relations program planning, collaborative public communication implementation, and continuous evaluation of school services. The school also utilizes digital media and direct communication in building harmonious relationships with the community. These strategies have a positive impact on increasing public trust, parent participation, and strengthening the school's image as an open, professional, and quality educational institution.